Evaluasi Kebijakan Jalur Penangkapan Dan Penempetan Alat Penangkapan Ikan (Studi Kasus Pada Nelayan Di Pelabuhan Karangantu Kota Serang, Banten) - Agus Koharudin; Ipah Ema Jumiati; Suwaib Amiruddin (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2021)
Regulation of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 71 / Permen-Kp / 2016, aims to realize the utilization of fish resources that are responsible, optimal and sustainable and to reduce conflicts over the use of fish resources based on the principles of management of fish resources. In implementing the regulation, it creates dynamics in fishing communities. The focus of this study examines the evaluation of the fishing lane policy and the placement of fishing gear on Fishermen in the Serang Port of Serang, Banten. The theoretical study in this study uses the William N. Dunn (1990) Policy Evaluation approach. The research method is a qualitative approach with a descriptive analytic research design. The results showed that the characteristics of the fishing track in the Karangantu Archipelago Fisheries Port, most fishermen had small scales. Government policy does not provide levies for fishermen who lean in the Port of Karangantu PPN. Government policies related to fishing gear have been issued Ministerial Regulation No. KKP. 71 of 2006, as a reference to bring order to fishermen in conducting operations in the Banten Bay Area and even throughout Indonesia. The policy is not implemented optimally because fishermen who operate in the port of Karangantu are mostly small-scale fishermen, while those who are regulated should pay attention to the characteristics of the type of boat and the size of the boat. The fishing area is carried out in a 4-mill marine area, and using fishing gear. The use of Cantrang or Arat Mini fishing gear similar to Trawling Tiger is actually not permitted and even there are no permits for fishermen who violate the rules of fishing gear, but these conditions are still used by fishermen. For enforcement, government support related to operational budgets is needed to support operations at sea.